The non-linear impact of risk tolerance on entrepreneurial profit and business survival - Melanie Koch; Lukas Menkhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
Entrepreneurs tend to be risk tolerant but is more risk tolerance always better? In a sample of about 2,100 small businesses, we find an inverted U-shaped relation between risk tolerance and profitability. This relationship holds in a simple bilateral regression and also when we control for a large set of individual and business characteristics. Apparently, one major transmission goes from risk tolerance via investments to profits. This is quite robust as it applies for past investments as well as planned investments. Considering business survival, we show, first, that less profitable businesses leave the market while moderately risk tolerant entrepreneurs survive more often. Second, the high risk-low profit part of the U-shaped relation seems to disappear among businesses being four years and older, indicating that such inferior risk-profit combinations disappear over time. These findings are important for the concept of business readiness trainings as the motivation (and ability) to take risks should potentially be accompanied by some warning that too much risk taking can be detrimental to long-term business success.
Keywords: D22; D81; L26; M21; 330; risk tolerance; entrepreneurs; profits; investments